Humoral and Cellular Immune Responses to SARS-CoV-2 mRNA Vaccination in Patients with Multiple Sclerosis: An Israeli Multi-Center Experience Following 3 Vaccine Doses - Milo, Ron; Staun-Ram, Elsebeth; Karussis, Dimitrios; Karni, Arnon; Hellmann, Mark A.; Bar-Haim, Erez; Miller, Ariel; , The Israeli Neuroimmunology Study Group on COVID-19 Vaccination in Multiple Sclerosis; Glass-Marmor, Lea; Volkovitz, Anat; Dishon, Sara; Dishon, Zeev; et al. (Frontiers in Immunology, 2022)
Background: Immunomodulatory/immunosuppressive activity of multiple sclerosis (MS) disease modifying therapies (DMTs) might affect immune responses to SARS-CoV-2 exposure or vaccination in patients with MS (PwMS). We evaluated the effect of DMTs on humoral and cell-mediated immune responses to 2 and 3 vaccinations and the longevity of SARS-Cov-2 IgG levels in PwMS. Methods: 522 PwMS and 68 healthy controls vaccinated with BNT162b2-Pfizer mRNA vaccine against SARS-CoV-2, or recovering from COVID-19, were recruited in a nation-wide multi-center study. Blood was collected at 3 time-points: 2-16 weeks and ~6 months post 2nd vaccination and 1-16 weeks following 3rd vaccination. Serological responses were measured by quantifying IgG levels against the spike-receptor-binding-domain of SARS-CoV-2, and cellular responses by quantifying IFNgamma secretion in blood incubated with COVID-19 spike-antigen. Results: 75% PwMS were seropositive post 2nd or 3rd vaccination. IgG levels decreased by 82% within 6 months from vaccination (p<0.0001), but were boosted 10.3 fold by the 3rd vaccination (p<0.0001), and 1.8 fold compared to ≤3m post 2nd vaccination (p=0.025). Patients treated with most DMTs were seropositive post 2nd and 3rd vaccinations, however only 38% and 44% of ocrelizumab-treated patients and 54% and 46% of fingolimod-treated patients, respectively, were seropositive. Similarly, in COVID-19-recovered patients only 54% of ocrelizumab-treated, 75% of fingolimod-treated and 67% of cladribine-treated patients were seropositive. A time interval of ≥5 months between ocrelizumab infusion and vaccination was associated with higher IgG levels (p=0.039 post-2nd vaccination; p=0.036 post-3rd vaccination), and with higher proportions of seropositive patients. Most fingolimod- and ocrelizumab-treated patients responded similarly to 2nd and 3rd vaccination. IFN-T-cell responses were detected in 89% and 63% of PwMS post 2nd and 3rd vaccination, however in only 25% and 0% of fingolimod-treated patients, while in 100% and 86% of ocrelizumab-treated patients, respectively. Conclusion: PwMS treated with most DMTs developed humoral and T-cell responses following 2 and 3 mRNA SARS-CoV-2 vaccinations. Fingolimod- or ocrelizumab-treated patients had diminished humoral responses, and fingolimod compromised the cellular responses, with no improvement after a 3rd booster. Vaccination following >5 months since ocrelizumab infusion was associated with better sero-positivity. These findings may contribute to the development of treatment-stratified vaccination guidelines for PwMS.